1999
DOI: 10.1182/blood.v94.1.368.413a47_368_371
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Trial of Retroviral-Mediated Transfer of arev-Responsive Element Decoy Gene Into CD34+Cells From the Bone Marrow of Human Immunodeficiency Virus-1–Infected Children

Abstract: Genetic modification of hematopoietic stem cells with genes that inhibit replication of human immunodeficiency virus-1 (HIV-1) could lead to development of T lymphocytes and monocytic cells resistant to HIV-1 infection after transplantation. We performed a clinical trial to evaluate the safety and feasibility of this procedure, using bone marrow from four HIV-1–infected pediatric subjects (ages 8 to 17 years). We obtained bone marrow, isolated CD34+ cells, performed in vitro transduction with a retroviral vect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 242 publications
(55 citation statements)
references
References 21 publications
1
54
0
Order By: Relevance
“…The mobilization of CD34 þ cells into the peripheral blood using G-CSF has been shown to be tolerated well in adults [Law et al, 1999] and children [Kohn et al, 1999] infected with HIV-1. Subsequent leukapheresis allows collection of not only monocytes but also therapeutic quantities of CD34 þ hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mobilization of CD34 þ cells into the peripheral blood using G-CSF has been shown to be tolerated well in adults [Law et al, 1999] and children [Kohn et al, 1999] infected with HIV-1. Subsequent leukapheresis allows collection of not only monocytes but also therapeutic quantities of CD34 þ hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of an RRE decoy sequesters the Rev protein, thereby blocking nuclear export of viral RNAs and thus virus replication (Bahner et al 1996). This RRE decoy has earlier been tested in a phase I clinical trial in which CD34 + stem cells were transduced ex vivo with a retroviral vector for the expression of the RNA inhibitor (Kohn et al 1999). There was no evidence that expression of the decoy affected cell function, but there were also no detectable changes in the subject's plasma HIV-1 level.…”
Section: Aptamers and Decoy Rnas As Antiviral Therapeuticsmentioning
confidence: 99%
“…In a phase I clinical trial, Kohn et al recently retrovirally introduced the Rev responsive element (RRE) RNA of HIV‐1 as a decoy into CD34 + hematopoetic progenitor cells from the bone marrow of HIV‐infected pediatric patients. The researchers could re‐infuse the changed cells into the patients without adverse effects 67. Previously, they had shown that expressing RRE RNA in such cells leads to the inhibition of HIV‐1 replication in the cells.…”
Section: Aptamers As Therapeutic Agents and Drugs‐to‐bementioning
confidence: 99%